Moby Multiple Language Lists of Common Words - Ward, Grady, 1951- (Salt Lake City, UT : Project Gutenberg, 2002)
"Moby Multiple Language Lists of Common Words" by Grady Ward is a compilation of word lists written in the early 21st century. This resource serves as a linguistic reference, featuring extensive vocabulary lists in several prominent languages, including French, German, Italian, Japanese, and Spanish. The aim of the book is to provide users with a comprehensive set of common words to aid in language study and usage. The content of this book comprises five language-specific lists, each enumerating a significant number of words in its respective language. For example, the French list contains over 138,000 words, while the German list boasts nearly 160,000. Each list is structured in a simple, accessible text format, making it easy for users to reference and utilize. Additionally, the book outlines instructions on how to download and access the files, emphasizing their public domain status and the utility of these lists for linguistic purposes. Overall, the work serves as a practical tool for language learners and linguists seeking to expand their vocabulary across multiple languages. (This is an automatically generated summary.)
Release date is 2002-05-01
Produced by Mike Pullen
Keywords: Words and phrase lists -- English